Improved representativeness of simulated climate using natural units and monthly resolution - Huebener, Heike; Gelhardt, Ulrike; Lang, Jürgen (Frontiers in Climate, 2022)
There is a considerable discrepancy between the temporal and spatial resolution required by climate impact researchers, policy makers and adaptation planners on the one hand and climate data providers on the other hand. While the spatial and temporal aggregation of climate data is necessary to increase the reliability and robustness of climate information, this often counteracts or even prohibits their use in adaptation planning. The problem is twofold (i.e. space and time) and needs to be approached accordingly. Climate impact research and adaptation planning are the domain of impact experts, politicians and planners, rather than climate experts. Thus, besides the spatial and temporal resolution, information also needs to be provided on platforms and in data formats that are easily accessible, easy to handle and easy to understand. We discuss possible steps towards bridging the gap using an example from the federal state Hesse (Germany) as illustration. We aggregate the climate data at a level of “natural units” and provide them as monthly data. We discuss the pros and cons of this kind of processed data for impact research and decision making. The spatial aggregation to “natural units” delivers suitable spatial aggregation, while maintaining physical geographic structures and their climatic characteristics. Within these “natural units”, single grid cell values are usable for climate impact analyses or decision making. The temporal resolution is monthly values, i.e. deviations of single month values for the scenario period from climatological monthly values in the (simulated) reference period. This resolution allows analyzing compound events or consecutive events on a monthly scale within a climatological (30-year) period.